2019
DOI: 10.1002/smll.201805545
|View full text |Cite
|
Sign up to set email alerts
|

WSe2 Photovoltaic Device Based on Intramolecular p–n Junction

Abstract: High quality p–n junctions based on 2D layered materials (2DLMs) are urgent to exploit, because of their unique properties such as flexibility, high absorption, and high tunability which may be utilized in next‐generation photovoltaic devices. Based on transfer technology, large amounts of vertical heterojunctions based on 2DLMs are investigated. However, the complicated fabrication process and the inevitable defects at the interfaces greatly limit their application prospects. Here, an in‐plane intramolecular … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
82
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 88 publications
(84 citation statements)
references
References 40 publications
2
82
0
Order By: Relevance
“…According to the power law I ph = c × P κ (c is a proportionality constant and κ is an empirical value), [24] the experimental results are linearly fitted with the value κ = 0.966, which exhibits a better linear fitting than previous reports. [18,25] This linear relationship between the photocurrent and the photoflux clarifies the fact that the measured electrical signals are dominated by the photogenerated charge carriers of the WSe 2 channel rather than the thermionic or tunneling current. The photoresponsivity of the device upon illumination is defined as R = ph I PS in units of A W −1 , where I ph is the photocurrent, P the incident light power density, and S the active area.…”
mentioning
confidence: 61%
See 3 more Smart Citations
“…According to the power law I ph = c × P κ (c is a proportionality constant and κ is an empirical value), [24] the experimental results are linearly fitted with the value κ = 0.966, which exhibits a better linear fitting than previous reports. [18,25] This linear relationship between the photocurrent and the photoflux clarifies the fact that the measured electrical signals are dominated by the photogenerated charge carriers of the WSe 2 channel rather than the thermionic or tunneling current. The photoresponsivity of the device upon illumination is defined as R = ph I PS in units of A W −1 , where I ph is the photocurrent, P the incident light power density, and S the active area.…”
mentioning
confidence: 61%
“…Figure b plots the photocurrent ( I ph = I illumination − I dark ) of the photodetectors ( V ds = 0.5 V) at various laser power densities ( P ). According to the power law I ph = c × P κ ( c is a proportionality constant and κ is an empirical value), the experimental results are linearly fitted with the value κ = 0.966, which exhibits a better linear fitting than previous reports . This linear relationship between the photocurrent and the photoflux clarifies the fact that the measured electrical signals are dominated by the photogenerated charge carriers of the WSe 2 channel rather than the thermionic or tunneling current.…”
mentioning
confidence: 74%
See 2 more Smart Citations
“…The current-rectifying characteristic can be modulated by V g , as shown in Figure S3. When V g = 10 V, a rectification ratio of 182 is obtained at V d = −1/+1 V. To specify the ideal factor (n) of the p-n diode, we fitted the experimental output results at different V g in the volt-ampere characteristic function [Equation (S1)] [29]. It is found that the experimental data fit well with the function, and a minimum value of 1.59 is achieved when V g = −30 V, as shown in Figure 2F and Figure S4.…”
Section: Resultsmentioning
confidence: 99%